2016
DOI: 10.1371/journal.pone.0162332
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Stemness, Paracrine, and Tumorigenic Characteristics of Highly Expanded, Minimally Passaged Adipose-Derived Stem Cells

Abstract: The use of adipose-derived stem cells (ADSC) in regenerative medicine is rising due to their plasticity, capacity of differentiation and paracrine and trophic effects. Despite the large number of cells obtained from adipose tissue, it is usually not enough for therapeutic purposes for many diseases or cosmetic procedures. Thus, there is the need for culturing and expanding cells in-vitro for several weeks remain. Our aim is to investigate if long- term proliferation with minimal passaging will affect the stemn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 77 publications
1
18
0
Order By: Relevance
“…In our study, we showed that expression patterns of cell surface markers on P3 cells were associated with MSCs [28][29][30]. El Atat et al [31] reported that ADSCs displaying CD90 and CD105 expressions were able to adhere to plastic surfaces under in vitro culture conditions. Moreover, these markers have also been used to determine multilineage differentiation capabilities of ADSCs [30].…”
Section: Discussionsupporting
confidence: 51%
“…In our study, we showed that expression patterns of cell surface markers on P3 cells were associated with MSCs [28][29][30]. El Atat et al [31] reported that ADSCs displaying CD90 and CD105 expressions were able to adhere to plastic surfaces under in vitro culture conditions. Moreover, these markers have also been used to determine multilineage differentiation capabilities of ADSCs [30].…”
Section: Discussionsupporting
confidence: 51%
“…Multilineage differentiation of ADMSCs: ADMSCs showed a differentiation capacity to become adipocytes, osteocytes, and chondrocytes. Adipogenic differentiation, osteogenic differentiation and chondrogenic differentiation was performed as previously described[24].…”
Section: Methodsmentioning
confidence: 99%
“…Adipose-derived stem cells (ASC) are easily accessible in large quantities from fat-tissue enabled by liposuction or abdominoplasty [ 6 , 13 , 16 ]. ASC proliferate rapidly [ 6 ] and possess a multi-lineage capacity, i.e., adipocytes, osteoblasts, chondrocytes [ 13 , 17 , 18 ]. Furthermore, ASC retain their mesenchymal potency over long-term culture [ 6 , 18 ] and promote the nerve regeneration similar to bone marrow stem cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASC proliferate rapidly [ 6 ] and possess a multi-lineage capacity, i.e., adipocytes, osteoblasts, chondrocytes [ 13 , 17 , 18 ]. Furthermore, ASC retain their mesenchymal potency over long-term culture [ 6 , 18 ] and promote the nerve regeneration similar to bone marrow stem cells [ 7 ]. In allogeneic transplantation, usage of ASC, like any other adult stem cells, benefits from their hypo-immunogenicity or immune-privilege by virtue of the reduced expression of HLA-DR class II histocompatibility antigen [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%